BEYOND THE RITUAL: LIFE’S DEEPER MEANING FOR CUPU KYAI PANJALA DEVOTEES - Handayani, Sonia Rachma; Nurjaman, Tabah Aris (Jurnal Psikologi Jambi, 2025)
This qualitative study explores the meaning of life among devotees of the Cupu Kyai Panjala ritual, a Javanese spiritual tradition in Gunungkidul, Indonesia. Employing a case study approach, data were collected through in-depth semi-structured interviews and non-participant observation with three devotees aged 40–70 years, who have participated in the ritual for over a decade. The findings reveal that the ritual fosters profound spiritual and social meaning, promoting values of patience, resilience, and sincerity. Devotees exhibit enhanced self-understanding, positive attitude changes, and strong commitment to preserving ancestral traditions. Social support from the ritual community further reinforces their sense of purpose. Drawing on Bastaman’s (2007) framework, the study highlights how consistent participation in the ritual shapes life goals, strengthens social bonds, and enhances psychological well-being. These findings underscore the vital role of local cultural practices in fostering meaningful lives among Kejawen practitioners.